OPTIMALISASI PENDIDIKAN DNEGAN METODE HOME VISIT UNTUK TK DAN SD DAN SOSIALISASI PROTOKOL COVID-19 DI DESA GADINGKULON DUSUN PRINCI KECAMATAN DAU KABUPATEN MALANG - Febrian , Rahmat; Fathin, Taqiyyah; Hanafiah, Aldi Bintang; Sofyana, Rizky Fauzan Putra; Mashita, Rizky Ayu (Bulletin of Community Service and Development, 2021)
This service aims to provide education optimization to the children of Gading Kulon Village not only in terms of academic knowledge but we also teach children the Koran and carry out monotheism, it is hoped that children will understand the importance of religious knowledge because of the problems that usually occur in the village if children are grown and do not understand their own religion, so they are increasingly lazy to learn the Koran and explore the science of religion. The activities that have been carried out consist of 3 programs, namely the first we teach kindergarten children with the Home Visit method where activities are carried out at students' homes. As for elementary school children, we teach online because of the ongoing pandemic problem. Our second program is to educate the Qur'anic learning by teaching the children of Dusun Perrinci the Koran and providing Islamic materials to strengthen the monotheism of the children of Dusun Perrinci. The third program besides us cleaning the prayer room, we also provide posters related to the SOP for praying during the pandemic and 5 steps to prevent Covid-19.